A flexible film with switchable adhesion based on pre-stretching femtosecond laser processing, a preparation method, a processing system and a device

CN122917540APending Publication Date: 2026-10-16HEFEI UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611334973.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]为了解决现有基于化学动态键的可切换粘附膜粘附力切换速度慢,难以满足微小易损器件高速精密转移应用需求的技术问题,本发明提供了一种基于预拉伸飞秒激光加工的粘附力可切换的柔性膜

Benefits of technology

1、本发明的柔性膜通过在双轴预拉伸的弹性体基底上进行飞秒激光横纵交叉扫描加工,预先构筑与基底应变状态绑定的网格状凹凸结构,再释放预拉伸使基底弹性回缩、带动表面凹凸结构同步压缩重构,形成自然状态下排布密集、真实接触面积大的高粘附界面;进行粘附力切换时,仅需对柔性膜施加机械拉伸(如背部环形顶压引发局部双轴拉伸),网格状凹凸结构的相邻扫描线间距便会随基底弹性形变同步瞬时增大,表面凹凸结构快速展开,界面真实接触面积在毫秒级时间内大幅降低,即刻完成从高粘附到低粘附的状态切换,撤去外力后又可随基底弹性回缩瞬间复位。相较于依赖动态化学键断裂与重构、单次切换需数秒的现有方案,本发明的粘附切换完全由弹性体机械形变驱动,无分子反应过程带来的滞后性,切换响应速度提升数个量级,可充分匹配微小易损器件高速批量转移的作业节拍;同时因全程不涉及化学反应与小分子基团迁移,还同步避免了器件化学污染、循环疲劳衰减等附带问题,更适配精密电子器件的低损伤、高可靠转移需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917540A_ABST
    Figure CN122917540A_ABST
Patent Text Reader

Abstract

The present application relates to the field of flexible dry adhesion interface material and micro-nano laser processing technology, and particularly relates to a flexible film with switchable adhesion based on pre-stretching femtosecond laser processing, a preparation method, a processing system and a device. First, an Ecoflex elastic film is prepared, biaxial pre-stretching is applied to the film and the stretching state is maintained; cross scanning is performed on the pre-stretched film by using a femtosecond laser, and a grid-shaped concave-convex structure is constructed on the surface; after the pre-stretching is released, the film elastically shrinks, the surface structure is compressed and reconstructed, and a strain-responsive adhesion interface is formed. In a natural state, the film is in a high adhesion state, and can stably pick up and transfer a device; after the film is locally stretched by annular top pressure on the back, the structure is unfolded, the real contact area is reduced, and low adhesion release is realized. The present application does not need a complex template and a phase change material, the process is simple, the response is fast, the performance is multi-dimensionally adjustable, and is suitable for low-damage precise transfer of micro small and fragile devices such as MicroLED.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of flexible dry adhesion interface materials and micro / nano laser processing technology, specifically to a flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing, a method for preparing a flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing, a processing system for a flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing, and a micro-device gripping and transfer device. Background Technology

[0002] In the precision transfer and assembly of tiny and fragile devices such as miniature LED chips, thin glass sheets, and semiconductor silicon wafers, traditional rigid grippers are prone to mechanical damage such as edge chipping and surface scratches, making it difficult to meet the assembly requirements of miniaturized and high-precision devices. As the pace of mass production in the industry continues to increase, the efficiency of transfer operations is becoming increasingly critical. Non-contact transfer solutions based on flexible adhesive films have become the mainstream development direction in the industry due to their low contact stress and strong adaptability. Achieving rapid and reversible switching of adhesion force is the core technical indicator to ensure transfer efficiency.

[0003] Currently, most mainstream switchable adhesive films use smooth, homogeneous elastomers or polymers as the matrix, relying on the intrinsic chemical dynamic bonds of the material to achieve controlled adhesion performance. For example, patent application CN202511400941.9 discloses a conductive ink, a reversible adhesive elastomer, and its preparation method. This method introduces a dynamic imine bond crosslinking system into a polymer matrix, relying on the reversible breaking and reconstruction of chemical bonds to adjust the interfacial adhesion force. The advantages of this approach are: reversible control of adhesion performance can be achieved without a complex mechanical drive structure; the material is homogeneous and smooth overall; the molding process is simple; and the dynamic crosslinking system endows the material with a certain self-healing ability, making it well-suited for static bonding scenarios such as flexible electronic bonding and wearable device attachment. However, this approach has a core limitation when applied to high-speed batch transfer scenarios: the switching of adhesion states depends on the chemical reaction process of breaking and reconstructing dynamic imine bonds. Due to the limitation of reaction kinetics, a single adhesion-desorption switch typically requires a response time of several seconds, and the transfer cycle is far lower than the needs of industrial mass production, making it difficult to match the operational efficiency requirements of high-speed batch transfer of micro-devices.

[0004] Overall, existing switchable adhesion schemes based on chemical dynamic bonds are inherently limited by the rate of chemical reactions, and generally suffer from the core defect of lag in adhesion switching response. They cannot achieve rapid and large-scale reversible switching of adhesion force through purely physical surface morphology deformation, making it difficult to meet the current industrial demand for high-speed transfer of micro-precision devices. Summary of the Invention

[0005] To address the technical problem that existing switchable adhesion films based on chemical dynamic bonds have slow adhesion force switching speeds, making them unsuitable for high-speed, precision transfer applications of small, fragile devices, this invention provides a flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing. Based on this flexible film, this invention also provides a method for preparing the flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing, a processing system for the flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing, and a device for gripping and transferring small devices.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A flexible film with switchable adhesion based on pre-stretched femtosecond laser processing includes a flexible elastomer film substrate, at least one surface of which is provided with a grid-like uneven structure formed by the cross arrangement of transverse and longitudinal scan lines. The grid-like concave-convex structure is formed by femtosecond laser scanning processing under a biaxial pre-tensioned state on the substrate, and completes compression reconstruction by elastic retraction as the substrate releases the pre-tension. When the flexible membrane is stretched and deformed by external force, the spacing between adjacent scanning lines of the grid-like uneven structure increases synchronously with the extension of the substrate; when the external force is removed, the spacing between adjacent scanning lines returns to its original position synchronously with the retraction of the substrate, so as to achieve reversible switching of adhesion force by changing the actual contact area with the target object.

[0007] As a further improvement to the above scheme: the flexible elastomer film substrate is any one of Ecoflex, PDMS, DragonSkin or SEBS-based elastomers.

[0008] As a further improvement to the above scheme: in the natural state of releasing pre-stretching, the spacing between adjacent scanning lines of the mesh-like uneven structure is 50~125μm; the thickness of the flexible elastomer film substrate is 0.5~2 mm; the surface roughness Ra of the mesh-like uneven structure increases with the number of femtosecond laser scans.

[0009] As a further improvement to the above scheme, the flexible membrane is configured to cause local biaxial stretching of the central contact area by back annular top pressure, so as to increase the spacing between adjacent scan lines of the grid-like concave-convex structure and reduce the interfacial adhesion force.

[0010] A method for preparing a flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing includes the following steps: S1. Preparation of flexible elastomer films; S2. Fix the flexible elastomer film and apply biaxial pre-stretching to keep the film in a tensile strain state; S3. While the film is under biaxial pre-stretching tension, a femtosecond laser is used to perform transverse and longitudinal cross-scanning on the surface of the film to be processed, forming a grid-like uneven structure on the surface. S4. Release the biaxial pre-stretch, and the film will elastically retract, causing the surface grid-like uneven structure to be compressed and reconstructed, resulting in a flexible film with switchable adhesion based on pre-stretched femtosecond laser processing.

[0011] As a further improvement to the above scheme, the specific content of step S1 is as follows: mix Ecoflex A glue and B glue in a mass ratio of 1:1 and stir evenly. After vacuuming to remove air bubbles, pour into a mold and let it stand to level. Cure at 60~70℃ for 25~35 minutes. After cooling, a flexible elastomer film is obtained.

[0012] As a further improvement to the above scheme: In step S2, the displacement of biaxial pre-stretching is 10~30mm, so that the in-plane stretch ratio of the film is 1.19~1.83, and the surface of the film to be processed after pre-stretching remains flat and wrinkle-free.

[0013] As a further improvement to the above scheme: in step S3, the processing parameters of the femtosecond laser are: repetition frequency 2~3kHz, scanning speed 50~200mm / s, and number of scans 5~20 times.

[0014] A processing system for a flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing, used to manufacture a flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing or a flexible film prepared by a method for preparing a flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing, comprising a biaxial stretching platform, a femtosecond laser processing unit, and a control unit. A biaxial stretching platform is used to hold flexible elastomer films and apply biaxial pre-stretching to the films to maintain their tensioned state. The femtosecond laser processing unit is used to output focused femtosecond laser light to the surface of the thin film to be processed and to perform scanning processing; The control unit is connected to the biaxial stretching platform and the femtosecond laser processing unit via signals, respectively. The control unit is configured to: while the film is held in a biaxial pre-stretched state, control the femtosecond laser processing unit to perform cross-scanning of the film surface in the transverse and longitudinal directions, forming a grid-like uneven structure on the film surface; and after processing, control the biaxial stretching platform to release the pre-stretch, so that the grid-like uneven structure on the film surface is compressed and reconstructed with elastic retraction.

[0015] A micro-device gripping and transfer device includes a transfer head body, an adhesive force switchable flexible membrane, and an annular top pressure drive assembly; The adhesive force switchable flexible film is an adhesive force switchable flexible film based on pre-stretched femtosecond laser processing, a flexible film prepared by a preparation method of adhesive force switchable flexible film based on pre-stretched femtosecond laser processing, or a flexible film prepared by a processing system for adhesive force switchable flexible film based on pre-stretched femtosecond laser processing. It is fixed to the lower bearing end face of the transfer head body in a grid-like concave-convex structure with the surface facing outward. The annular top pressure drive assembly is located inside the transfer head body and includes an annular top pressure member that can reciprocate along the transfer head axis. The lower annular surface of the annular top pressure member faces the back center area of ​​the flexible film with switchable adhesion. When the annular top pressure component is in the retracted position, the adhesion force can be switched so that the flexible membrane remains in a natural stress-free state, exhibiting high adhesion characteristics to adsorb and pick up tiny devices. When the annular pressing member is in the extended position, it presses downward on the central area of ​​the back of the flexible membrane, causing local biaxial stretching of the corresponding area of ​​the flexible membrane. This increases the spacing between adjacent scan lines of the grid-like concave-convex structure and reduces the interfacial adhesion to release the micro-device.

[0016] Compared with the prior art, the beneficial effects of the present invention are: 1. The flexible membrane of the present invention is processed by femtosecond laser cross-scanning on a biaxially pre-stretched elastomer substrate to pre-construct a grid-like uneven structure bound to the strain state of the substrate. Then, the pre-stretching is released to allow the substrate to elastically retract, causing the surface uneven structure to be synchronously compressed and reconstructed, forming a high-adhesion interface with a dense arrangement and a large actual contact area in its natural state. When switching the adhesion force, only mechanical stretching (such as local biaxial stretching caused by back annular top pressure) needs to be applied to the flexible membrane. The spacing between adjacent scan lines of the grid-like uneven structure will increase instantaneously with the elastic deformation of the substrate. The surface uneven structure will quickly unfold, and the actual contact area of ​​the interface will be greatly reduced in milliseconds, instantly completing the state switch from high adhesion to low adhesion. After the external force is removed, it can be instantly reset with the elastic retraction of the substrate. Compared to existing solutions that rely on dynamic chemical bond breaking and reconstruction and require several seconds for a single switch, the adhesion switching of this invention is entirely driven by the mechanical deformation of the elastomer, eliminating the lag caused by molecular reaction processes. The switching response speed is improved by several orders of magnitude, which can fully match the operational cycle of high-speed batch transfer of small and fragile devices. At the same time, since no chemical reaction or small molecule group migration is involved in the entire process, it also avoids the associated problems such as device chemical contamination and cyclic fatigue decay, making it more suitable for the low-damage and high-reliability transfer requirements of precision electronic devices.

[0017] 2. The preparation method adopts a process route of "pre-stretching-laser processing-release reconstruction", which eliminates the need for expensive photolithography templates and complex wet etching processes. It can precisely construct a grid-like uneven structure on the surface of the elastomer by femtosecond laser direct writing. The process steps are simple, the processing accuracy is high, and the pattern flexibility is strong. At the same time, this method can quantitatively control the surface morphology and adhesion properties of the finished film by adjusting parameters such as the number of laser scans, the scan line spacing, and the pre-stretching displacement. The parameter control dimensions are rich, and products with different performance specifications can be quickly customized. Moreover, the pre-stretching-release structural reconstruction design is ingenious, so that the surface morphology and substrate strain are naturally bound together, providing a stable structural foundation for rapid switching of adhesion force in subsequent use.

[0018] 3. The processing system integrates biaxial stretching clamping, femtosecond laser processing, and multi-module collaborative control, enabling the entire process of film stretching, laser etching, and load release to be completed at the same workstation, avoiding precision and efficiency losses caused by process flow. The control unit can synchronously and precisely regulate the stretching rate, laser parameters, and scanning path, resulting in excellent processing consistency and stability, ensuring uniform and stable adhesion performance of each batch of products during mass production. At the same time, the system supports a wide range of adjustments for film thickness, stretch ratio, and laser parameters, making it compatible with the processing needs of various specifications of elastomer films and possessing strong mass production adaptability and process expansion space.

[0019] 4. The gripping and transfer device highly integrates the strain-responsive flexible membrane and the annular top pressure drive component into the transfer head. The overall structure is compact and can be directly connected to existing precision transfer production lines without the need for additional external auxiliary equipment such as temperature field and electric field, which greatly reduces system complexity and operation and maintenance costs. The device achieves adhesion switching by local deformation caused by mechanical top pressure. It has fast response speed and strong controllability. The contact stress is uniform and there is no rigid clamping during the picking and releasing process, which can effectively avoid edge cracking and surface scratches of small and vulnerable devices. At the same time, the local stretching mode of the annular top pressure can precisely control the action area, enabling the independent release of single devices or small areas, which is suitable for the high-precision assembly requirements of micro devices. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of a femtosecond laser micro / nano fabrication system.

[0021] Figure 2 A flowchart illustrating the preparation and workflow of a flexible membrane with switchable adhesion.

[0022] Figure 3 This is a schematic diagram of the Ecoflex thin film pre-stretching femtosecond laser processing flow.

[0023] Figure 4 This is a schematic diagram of the prepared flexible membrane structure.

[0024] Figure 5This is a schematic diagram illustrating the adhesion switching working principle of a flexible membrane with switchable adhesion force.

[0025] In the figure: 10, flexible elastomer film substrate; 20, grid-like uneven structure. Detailed Implementation

[0026] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0027] This specific implementation focuses on a switchable adhesion flexible film based on pre-stretched femtosecond laser processing. It sequentially describes the overall architecture of the supporting processing system, the composition of each functional unit, and the collaborative control logic. It details the complete fabrication process flow: "substrate preparation—biaxial pre-stretching—pre-stretched femtosecond laser cross-scanning—release and retraction structure reconstruction," and provides multiple parameterized examples under different scan line spacing, scan counts, film thickness, and pre-stretch displacement. Simultaneously, experimental characterization clarifies the control laws of scan count on surface roughness, scan line spacing on adhesion switching performance, and film thickness and stretch displacement on film stretch ratio, verifying that the surface morphology and adhesion performance of the flexible film can be flexibly controlled in multiple dimensions through process parameters. Furthermore, it introduces the structural composition of a micro-device gripping and transfer device integrating this flexible film, fully explaining the working process of a high-adhesion pickup device in its natural state and low-adhesion release achieved by local biaxial stretching induced by back annular top pressure. It also points out the application value of this solution in low-damage precision transfer scenarios for micro-LED chips, thin glass sheets, silicon wafers, and other small and vulnerable devices.

[0028] I. Processing system for flexible films with switchable adhesion

[0029] The processing system of this embodiment is used to prepare a flexible membrane with switchable adhesion force and strain response characteristics. The whole system includes a biaxial stretching platform, a femtosecond laser processing unit, a three-dimensional moving stage and a control unit.

[0030] (I) Overall System Architecture

[0031] like Figure 1As shown, the biaxial stretching platform is fixedly installed on the surface of the three-dimensional moving stage, used to clamp the flexible elastomer film and apply in-plane biaxial pre-stretching to it, so that the film maintains a stable tensile strain state; the output optical path of the femtosecond laser processing unit is aligned with the processing station of the three-dimensional moving stage, used to output focused femtosecond pulse laser to the surface of the film to be processed and perform programmable scanning processing; the control unit is electrically connected to the biaxial stretching platform, the femtosecond laser processing unit and the three-dimensional moving stage respectively, used to coordinate the control of the action timing and operating parameters of each module.

[0032] (ii) Femtosecond laser processing unit

[0033] The femtosecond laser processing unit specifically includes a femtosecond laser, a mirror group, an aperture, a half-wave plate, a GlanTell prism, a scanning galvanometer, and an F-θ lens, with each optical element arranged sequentially along the optical path.

[0034] Femtosecond lasers: used to output ultrashort pulse lasers as an energy source for surface microstructure processing; Reflector group: Composed of multiple plane mirrors, used to adjust the propagation direction of the laser beam and guide the laser through subsequent optical elements in sequence; Aperture: Used to spatially shape the incident beam, filter out stray light at the edge of the beam, and obtain a well-defined processing beam. Half-wave plate and Glan Taylor prism: The two work together to control the polarization state and output energy of the laser, so as to achieve continuous adjustment and precise selection of processing energy; Scanning galvanometer: Composed of two sets of high-speed deflectable galvanometers, used to control the scanning path of the laser beam on the thin film surface, realizing programmable scanning in the horizontal and vertical directions; F-θ lens: Located on the output side of the scanning galvanometer, it is used to focus the deflected laser beam onto the surface of the thin film to be processed and to ensure that the focused spot energy is uniform at each position within the scanning range.

[0035] During operation, the pulsed laser output from the femtosecond laser is adjusted in propagation direction by a group of mirrors, passes through an aperture to complete beam shaping, passes through a half-wave plate and a Glan-Taylor prism to complete polarization control and energy screening, then enters a scanning galvanometer to achieve two-dimensional scanning deflection, and finally acts on the surface of a pre-stretched flexible elastomer film after being focused by an F-θ lens to complete the micro-nano structure fabrication.

[0036] (iii) Control Unit

[0037] The control unit is configured to execute the following control logic: 1. Pre-stretch control: Before laser processing, the biaxial stretching platform is controlled to apply biaxial pre-stretch to the film according to the set displacement, so that the film reaches the target stretch ratio and maintains the tension state, while ensuring that the surface of the area to be processed is flat and wrinkle-free. 2. Scanning process control: While the film is continuously held in a biaxial pre-stretched state, the femtosecond laser is controlled to output pulsed laser with set parameters, and the scanning galvanometer is controlled to perform cross-scanning with the transverse and longitudinal directions perpendicular to each other along a preset path to form a grid-like uneven structure 20 on the film surface; 3. Release and Reconstruction Control: After the laser processing is completed, the femtosecond laser is controlled to stop emitting light, and then the biaxial stretching platform is controlled to slowly and uniformly release the pre-stretch load, so that the film completes the compression reconstruction of the surface grid-like uneven structure 20 during the elastic recovery process, and finally obtains a flexible film product with switchable adhesion force based on pre-stretched femtosecond laser processing.

[0038] In addition, the control unit also supports independent adjustment of parameters such as the repetition frequency, scanning speed, number of scans, and scanning line spacing of the femtosecond laser, as well as the stretching displacement and stretching rate of the biaxial stretching platform, to adapt to different processing requirements.

[0039] II. Preparation method of flexible film with switchable adhesion based on pre-stretched femtosecond laser processing

[0040] like Figure 2 and Figure 3 As shown, this embodiment uses the above-mentioned processing system to prepare a flexible film with switchable adhesion. The process follows the logic of "pre-stretching tension - pre-stretched state laser processing - release retraction and reconstruction". The finished film can achieve reversible switching of adhesion properties by stretching it again. The specific preparation process is as follows.

[0041] Example 1: Basic preparation process (preferred parameters)

[0042] S1. Preparation of flexible elastomer films

[0043] Prepare a flat and clean flat mold. First, clean the surface of the mold to remove dust, oil and other impurities to avoid affecting the quality of film forming.

[0044] Ecoflex silicone rubber was selected as the substrate, and its A and B components were mixed at a mass ratio of 1:1 and stirred thoroughly until the two components were completely and uniformly mixed. The mixture was then placed in a vacuum pump and evacuated for 3 minutes to completely remove air bubbles introduced during stirring. After degassing, the mixture was poured evenly into a mold, allowing it to spread naturally and level itself. Once the surface was completely smooth, the mold was placed in a 65°C oven for curing for 30 minutes. After curing, the mold was removed, cooled to room temperature, and demolded to obtain a 2mm thick Ecoflex flexible elastomer film.

[0045] S2, Film clamping and biaxial pre-stretching

[0046] After demolding, the Ecoflex film is flattened and fixed in the clamping position of the biaxial stretching platform. The biaxial pre-stretch displacement is set to 20mm through the control unit, and the biaxial stretching platform is started to apply tensile loads to the film simultaneously in two mutually perpendicular directions. After stretching, the film is kept under tension to ensure that the surface of the area to be processed is flat and free of obvious wrinkles or warping, thus providing a stable processing base for subsequent laser processing.

[0047] S3, Femtosecond laser cross-scanning processing under pre-stretched state

[0048] The processing path file is called by the control unit, the processing area is set to 15mm×15mm, and the scanning path is a grid of intersecting lines that are perpendicular to each other in the horizontal and vertical directions; the X, Y, and Z positions of the three-dimensional moving stage are adjusted so that the focus of the femtosecond laser is accurately aligned with the surface of the thin film to be processed.

[0049] Set the femtosecond laser processing parameters: repetition rate 2.5 kHz, scanning speed 50 mm / s, number of scans 6, and scan line spacing 100 μm. After setting the parameters, use the preview function to confirm that the processing path matches the processing area and that the processing range is located in the central region of the pre-stretched film.

[0050] After confirming that everything is correct, the processing program is started. The femtosecond laser scans and processes the thin film surface according to the preset cross path. The laser acts on the thin film surface to produce local ablation and thermal-mechanical effects, forming a regular grid-like uneven structure 20 on the pre-stretched thin film surface.

[0051] S4. Releasing Pre-Stretch and Structural Reconstruction

[0052] After processing, the femtosecond laser is stopped from emitting light, and the biaxial stretching platform is slowly and uniformly released to allow the Ecoflex film to gradually elastically shrink from a stretched state to a natural stress-free state.

[0053] During the film retraction process, the grid-like uneven structure 20 formed by laser processing is compressed and reconstructed synchronously with the substrate. The spacing between adjacent scanning lines decreases synchronously with the substrate retraction, and the surface uneven morphology is further densified. Finally, a highly adhesive surface with strain response characteristics is formed in the natural state, that is, a flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing is obtained.

[0054] Example 2: Preparation variants with different scan line spacings

[0055] The difference between this embodiment and Embodiment 1 is that the scan line spacing in step S3 is set to 75μm, 100μm, and 125μm respectively, while the remaining preparation parameters and operating procedures are consistent with Embodiment 1. By adjusting the scan line spacing, the surface morphology and high adhesion value of the finished film in its natural state can be controlled to adapt to the transfer requirements of target objects of different weights.

[0056] Example 3: Preparation variants with different scan numbers

[0057] The difference between this embodiment and Embodiment 1 is that in step S3, the number of femtosecond laser scans is set to 15, 20, 25, and 30, respectively, and the scan line spacing is fixed at 50 μm. All other preparation parameters and operating procedures remain consistent with Embodiment 1. By adjusting the number of scans, the surface roughness and unevenness of the film can be controlled, thereby optimizing the switching amplitude of the adhesion force.

[0058] Example 4: Preparation variants with different film thicknesses and pre-stretch displacements

[0059] The difference between this embodiment and Embodiment 1 is that Ecoflex films with thicknesses of 0.5 mm, 1 mm, 1.5 mm, and 2 mm are used, and corresponding biaxial pre-stretch displacements are set to 10 mm, 15 mm, 20 mm, 25 mm, and 30 mm. All other preparation parameters and operating procedures remain the same as in Embodiment 1. By matching different film thicknesses and pre-stretch displacements, finished films with different pre-strain levels and structural reconstruction amplitudes can be obtained, achieving different adhesion force switching properties.

[0060] III. Preparation of the Adhesion-Switching Flexible Film and its Performance Characterization

[0061] The adhesion-switching flexible film obtained by the above preparation method, such as... Figure 4 As shown, the substrate includes a flexible elastomer film substrate 10, at least one surface of which is provided with a grid-like uneven structure 20 formed by mutually perpendicularly intersecting transverse and longitudinal scan lines. The grid-like uneven structure 20 has a distinct strain response characteristic: since the structure is formed in the tensile state of biaxial pre-stretching of the substrate, after the pre-stretching is released and compression reconstruction is completed, the morphology of the structure is highly bound to the strain state of the substrate.

[0062] When the flexible membrane is in a natural, unforced release state, the grid-like uneven structure 20 is compressed and reconstructed as the substrate retracts. The spacing between adjacent scan lines is small, and the surface uneven structure is densely arranged. When it comes into contact with the target object, it can form a large real contact area and exhibits high adhesion characteristics. When the flexible membrane is stretched and deformed by external force, the spacing between adjacent scanning lines of the mesh-like uneven structure 20 increases synchronously with the extension of the substrate. The uneven structure on the surface is unfolded, the actual contact area is significantly reduced, and it exhibits low adhesion characteristics. When the external force is removed, the spacing between adjacent scan lines is reset synchronously with the elastic retraction of the substrate, and the surface returns to a high adhesion state. This allows for reversible switching of adhesion force by changing the actual contact area.

[0063] In a preferred embodiment, the flexible elastomer film substrate 10 can be any one of Ecoflex, PDMS, DragonSkin, or SEBS-based elastomers, as long as it has high elasticity and reversible stretch recovery characteristics; in the natural state after releasing pre-stretching, the spacing between adjacent scan lines of the mesh-like uneven structure 20 is 50~125μm; the thickness of the flexible elastomer film substrate 10 is 0.5~2mm; and the surface roughness Ra of the mesh-like uneven structure 20 is in the range of 3~8μm.

[0064] (II) The effect of the number of scans on surface morphology and roughness

[0065] To verify the effect of the number of femtosecond laser scans on the surface roughness of Ecoflex films, the surface of pre-stretched Ecoflex films was processed by setting the number of femtosecond laser scans to 15, 20, 25, and 30, respectively, while keeping the scanning speed at 200 mm / s, the line spacing at 50 μm, and the transverse and longitudinal cross-scanning method unchanged.

[0066] After machining and releasing the pre-stretched state, the morphology of the machined surface under different scan numbers was characterized using a three-dimensional laser confocal microscope. The results show that as the number of scans increased from 15 to 30, the rough structure of the Ecoflex surface gradually intensified, the surface height undulations became more pronounced, and the regular array-like rough structure became clearer. Simultaneously, the surface roughness Ra gradually increased with the number of scans. Specific test data are shown in Table 1.

[0067] Table 1. Surface roughness test results of Ecoflex films under different scan numbers

[0068] As shown in Table 1, under the same scanning speed and scanning spacing, the number of femtosecond laser scans can effectively control the surface roughness of the Ecoflex film. With increasing scan count, the cumulative ablation and thermo-mechanical effects of the laser on the material surface are enhanced, resulting in a more pronounced uneven structure in the processed area. This rough structure helps to alter the actual contact area of ​​the Ecoflex film under unstretched and top-stretched conditions, thereby improving the adhesion switching effect.

[0069] (III) The effect of scan line spacing on adhesion switching performance

[0070] To further verify the effect of femtosecond laser scanning line spacing on the adhesion switching performance of Ecoflex flexible film, a 2mm thick Ecoflex film was used as the test object. Under the condition of keeping the transverse and longitudinal cross scanning mode unchanged, the scanning line spacing was set to 75μm, 100μm and 125μm respectively, and the adhesion force in the pre-stretched state and the stretched state was tested. The test data are shown in Table 2.

[0071] Table 2. Adhesion test results of Ecoflex flexible film under different scan line spacings.

[0072] As shown in Table 2, the scan line spacing has a significant impact on the high adhesion state of the Ecoflex flexible film. In the 2mm thick Ecoflex film, as the scan line spacing increases from 75μm to 125μm, the adhesion force in the pre-stretched state increases from 55mN to 608mN, while the adhesion force in the stretched state remains basically stable at 22-24mN. This indicates that the structure can maintain a low release adhesion force while adjusting the adhesion force in the high adhesion state by adjusting the line spacing. These results demonstrate that both the femtosecond laser line spacing and the stretched state affect the interfacial adhesion force, enabling a switchable effect from high adhesion to low adhesion.

[0073] (iv) Effects of film thickness and biaxial tensile displacement on draw ratio

[0074] To further clarify the tensile response of Ecoflex films of different thicknesses on a biaxial stretching platform, this invention conducted biaxial tensile tests on Ecoflex films with thicknesses of 2 mm, 1.5 mm, 1 mm, and 0.5 mm. During the tests, the biaxial tensile displacements were set to 10 mm, 15 mm, 20 mm, 25 mm, and 30 mm, and the corresponding stretch ratios were recorded.

[0075] The results show that, under the same film thickness, the stretch ratio of the Ecoflex film gradually increases with the increase of biaxial stretch displacement. Under the same stretch displacement, the thinner Ecoflex film usually exhibits a slightly higher stretch ratio, indicating that the film thickness affects the degree of deformation of the film during biaxial stretching. This result suggests that the pre-strain degree of the film can be controlled by adjusting the Ecoflex film thickness and the biaxial pre-stretch displacement, thereby further influencing the degree of surface structure reconstruction and its adhesion switching performance after femtosecond laser processing. Specific test data are shown in Table 3.

[0076] Table 3. Test results of the stretch ratio of Ecoflex films with different film thicknesses and biaxial tensile displacements.

[0077] As shown in Table 3, when the biaxial tensile displacement increases from 10 mm to 30 mm, the stretch ratio of the 2 mm thick Ecoflex film increases from 1.19 to 1.78; the stretch ratio of the 1.5 mm thick Ecoflex film increases from 1.20 to 1.80; the stretch ratio of the 1 mm thick Ecoflex film increases from 1.21 to 1.81; and the stretch ratio of the 0.5 mm thick Ecoflex film increases from 1.22 to 1.83. This indicates that under the biaxial tensile platform conditions used in this invention, the Ecoflex film can achieve a stable and adjustable pre-stretch state.

[0078] The stretch ratio test results provide a basis for the selection of subsequent femtosecond laser processing parameters. Preferably, the biaxial pre-stretch displacement can be set to 10-30 mm, more preferably 20-30 mm; the Ecoflex film thickness can be set to 0.5-2 mm, and can be selected according to the target object size, required adhesion force and release conditions, so that the film obtains a more obvious but still relatively stable pre-strain state, which is conducive to the effective reconstruction of the laser-processed structure after the pre-stretch is released, and the adhesion force switching can be achieved when stretched again or subjected to back pressure.

[0079] IV. Micro-device gripping and transfer device

[0080] The adhesive force switchable flexible film of the present invention can be integrated into a micro-device gripping and transfer device. It achieves millisecond-level reversible switching of adhesive force through pure mechanical deformation, and combines a ring-shaped progressive peeling effect to complete the low-damage precision transfer of micro-vulnerable devices.

[0081] The micro-device gripping and transfer device has a coaxial and axisymmetric structure, consisting of three parts from top to bottom: a transfer head body, a flexible film assembly with switchable adhesion, and a ring-shaped top pressure drive assembly. The upper part of the device can be connected to industrial robots, precision displacement stages, or array-type transfer modules via a standard mechanical interface, while the lower part's flexible film working surface with switchable adhesion directly contacts the target device. The overall outer diameter can be customized from 12 to 20 mm according to the application scenario, adapting to single-device pickup or small-area array pickup requirements.

[0082] (a) Transfer head body

[0083] The transfer head body adopts a hollow stepped cylindrical structure, made of aluminum alloy or stainless steel, and the surface is anodized or nickel-plated, combining lightweight and structural rigidity.

[0084] The upper end of the transfer head body is a standard installation interface, which can be equipped with external threads, flanges or quick-connect couplings for rigid connection with external displacement actuators; The middle section of the transfer head body is a receiving cavity for installing the drive and guide components of the annular top pressure drive assembly. The inner wall of the cavity is provided with an axial positioning step and a wiring groove. The lower end of the transfer head body is a bearing end face, with a circular through hole at the center for the annular top-pressing component to pass through. A ring-shaped positioning groove with a depth of 0.2~0.5mm is machined around the outer edge of the bearing end face. The inner diameter of the annular positioning groove matches the effective working area diameter of the adhesive-switching flexible membrane. Three to six micro-threaded holes are evenly distributed circumferentially at the bottom of the annular positioning groove for locking the annular pressure ring. The diameter of the circular through hole on the bearing end face is 7~9mm, and the inner diameter of the accommodating cavity matches the outer diameter of the linear guide bushing and the annular top-pressing component, forming a complete closed dimensional chain to ensure coaxial assembly of all components without interference.

[0085] (ii) Assembly structure of flexible membrane with switchable adhesion

[0086] The flexible membrane with switchable adhesion is assembled at the lower end of the transfer head body with its grid-like uneven structure facing outwards and its smooth back facing inwards. It adopts an assembly scheme of "edge pressing and fixing, and free deformation at the center". The specific structure is as follows: 1. Positioning and clamping structure The annular region (1.5~2mm wide) of the edge of the switchable adhesion flexible membrane is embedded in the annular positioning groove at the lower end of the transfer head body. The depth of the annular positioning groove is adapted to the thickness of the switchable adhesion flexible membrane, ensuring that the working surface of the switchable adhesion flexible membrane is flush with the end face reference surface of the transfer head body after assembly. An annular pressure ring is set above the annular positioning groove. The annular pressure ring is made of stainless steel with a thickness of 0.8~1mm. Countersunk holes corresponding to the micro-threaded holes are opened along the circumference, and it is evenly locked by M1.2~M1.6 micro screws.

[0087] After locking, the lower end face of the annular pressure ring is slightly lower than the working surface of the adhesive force switchable flexible membrane by 0.1~0.2mm. This ensures that the edges are firmly pressed without loosening and prevents the annular pressure ring from protruding and interfering with the pickup of the device. This assembly method only restricts the edge freedom of the adhesive force switchable flexible membrane, while the effective working area with a diameter of 8~10mm in the center is completely free and can undergo local biaxial tensile deformation without obstruction under top pressure.

[0088] 2. Pre-tensioning and sealing design

[0089] During assembly, the switchable adhesion flexible membrane is first laid flat in the annular positioning groove. During the locking of the annular pressure ring, a 0.5%~1% in-plane micro-pretension force is applied to the switchable adhesion flexible membrane to ensure a smooth, wrinkle-free working surface in its natural state, without altering its original compression and reconstruction morphology. A thin silicone rubber sealing ring can be added between the annular pressure ring and the bottom surface of the annular positioning groove. This serves two purposes: firstly, it fills the assembly gap, improves edge sealing, and prevents dust from entering the cavity; secondly, it provides uniform clamping force through elastic compression, preventing edge slippage of the switchable adhesion flexible membrane during repeated stretching and retraction.

[0090] 3. Friction reduction and protection on the back side

[0091] After plasma surface pretreatment, the smooth back surface (unprocessed surface) of the switchable adhesion flexible membrane is coated with a 5-10 μm thick polytetrafluoroethylene (PTFE) anti-friction coating. This coating covers the entire contact area of ​​the annular pressure member, reducing sliding friction between the member and the back surface of the membrane during reciprocating motion, thus minimizing film wear and extending cycle life. The coating is prepared using a spraying process, with uniformity error controlled within ±1 μm to avoid affecting the consistency of localized tensile deformation.

[0092] (III) Annular Top Pressure Drive Assembly

[0093] The annular top pressure drive assembly is coaxially mounted within the hollow cavity of the transfer head body. It outputs bidirectional axial displacement, driving localized biaxial stretching in the central region of the adhesive-switching flexible membrane. Controllable device release is achieved through the combined effect of reduced interfacial contact area and annular progressive peeling. The annular top pressure drive assembly includes a bidirectional linear drive unit, a spherical floating joint, a linear guide bushing, and an annular top pressure component.

[0094] 1. Bidirectional linear drive unit

[0095] The bidirectional linear drive unit uses a miniature piezoelectric ceramic actuator or a miniature linear servo motor, which is fixedly installed on the axial positioning step on the upper part of the receiving cavity. It can actively perform bidirectional extension and retraction actions, and has both top pressure drive and reset functions, without the need for additional reset elastic elements.

[0096] The bidirectional linear drive unit has an output stroke of 0.5~2mm and a displacement resolution of up to 1μm, enabling precise control of the top pressure depth and thus quantitative adjustment of the adhesion force switching amplitude. The power supply and control lines of the bidirectional linear drive unit are led out through the wiring groove on the side wall of the transfer head body and connected to the external control module.

[0097] 2. Spherical floating joint

[0098] The output end of the bidirectional linear drive unit is rigidly connected to the upper end of the annular top-pressing component through a spherical floating joint. The spherical floating joint can automatically compensate for assembly coaxiality errors, avoid radial off-center load during pressing and resetting, and ensure uniform force on the lower end face of the annular top-pressing component.

[0099] 3. Linear guide bushing

[0100] A polyimide linear guide bushing is installed between the outer wall of the annular top pressure component and the inner wall of the receiving cavity. The linear guide bushing and the annular top pressure component adopt an H7 / h6 clearance fit, which restricts the motion freedom of the annular top pressure component throughout the process, ensuring that the extension and retraction actions are smooth along the axial direction, and the radial runout is controlled within 0.02mm.

[0101] 4. Annular top pressure component

[0102] The annular top-pressing component is a hollow cylindrical structure of equal diameter, made of hard aluminum alloy or zirconia ceramic. The lower annular surface is the working top-pressing surface, directly facing the central area of ​​the back of the flexible membrane with switchable adhesion. The upper end is equipped with a standard connection interface for direct docking with the spherical floating joint. The outer diameter of the annular top-pressing component is 6~8mm, the inner diameter is 4~6mm, and the wall thickness is 1~1.5mm. The inner and outer edges of the lower end face are machined with rounded corners of 0.3~0.8mm radius, and the end face is mirror polished with a surface roughness Ra≤0.2μm to avoid scratching or snagging the back of the flexible membrane with switchable adhesion during reciprocating motion.

[0103] The outer wall of the annular top pressure component is fully engaged with the linear guide bushing, without any additional flange structure, resulting in a more compact axial dimension and effectively reducing the overall height of the transfer head body.

[0104] The above-mentioned corresponding size parameters can be adjusted adaptively according to the actual situation.

[0105] (iv) Assembly process flow of the micro-device gripping and transfer device

[0106] 1. Press the linear guide bushing into the hollow cavity of the transfer head body to complete the positioning and fixation; 2. Insert the annular top pressure component into the cavity through the circular through hole at the lower end of the transfer head body, and then install the spherical floating joint and the bidirectional linear drive unit in sequence. After locking and fixing, confirm the coaxiality of the movement. 3. Lay the flexible film with switchable adhesion flat in the annular positioning groove at the lower end of the transfer head body, adjust the position to ensure coaxiality, place the annular pressure ring and tighten the micro screws evenly in diagonal order, and apply the set micro pre-tension force. 4. Connect the power line and control line, conduct no-load debugging, verify the top pressure stroke, reset position and end face flatness, and complete the assembly after confirming that there is no jamming or deviation.

[0107] (V) Working process of the micro-device grasping and transfer device

[0108] 1. High adhesion pickup state

[0109] In the initial state, the bidirectional linear drive unit is in the retracted zero position, driving the annular top-pressing component to synchronously remain in the retracted position. The lower end face of the annular top-pressing component maintains micro-contact with the back of the adhesive force switchable flexible film or leaves a gap of 0.05~0.1mm. At this time, the adhesive force switchable flexible film is in a natural stress-free state, and the surface grid-like uneven structure exhibits a compressed reconstruction shape. The spacing between adjacent scan lines is small, the actual contact area is large, and it exhibits high adhesion characteristics.

[0110] When picking up a device, the external mechanism drives the transfer head body to descend vertically, so that the working surface of the flexible film with switchable adhesion force can be smoothly attached to the upper surface of the target device. A slight pre-pressure (5~20mN) is applied to ensure full contact at the interface. Then, the transfer head body is controlled to rise, and the target device can be stably lifted by relying on van der Waals force and viscoelastic adhesion force to complete the picking and spatial transfer.

[0111] 2. Low adhesion release state

[0112] When the target device moves with the transfer head body to directly above the target station, the control module outputs a drive signal to the bidirectional linear drive unit. The bidirectional linear drive unit pushes the annular top pressure component downwards, and the center area of ​​the back of the flexible film can be switched by the adhesion force of the lower annular surface.

[0113] The top-pressing process generates a dual desorption effect: First, due to the annular constraint, the central contact area of ​​the adhesive force-switching flexible film protrudes downwards, resulting in in-plane bidirectional stretching. The spacing between adjacent scan lines of the grid-like uneven structure increases synchronously with the substrate extension, the surface uneven structure unfolds, and the actual contact area between the film and the target device drops sharply, significantly reducing the interfacial adhesion. Second, the annular top-pressing surface and the central free area form a continuous deformation gradient, causing the contact interface between the flexible film and the device to gradually peel off from the annular edge towards the center. This progressive peeling effect further disrupts the interfacial adhesion, ultimately allowing the target device to smoothly detach from the surface of the adhesive force-switching flexible film and fall vertically to the target station, achieving low-damage, highly reliable, and controllable release. By controlling the top-pressing displacement, the adhesion attenuation rate and peeling rate can be quantitatively adjusted to adapt to the release requirements of devices of different weights.

[0114] After release, the bidirectional linear drive unit actively performs a retraction action, driving the annular top-pressure component to synchronously reset to the zero position, removing the top-pressure load on the adhesive force switchable flexible membrane. The adhesive force switchable flexible membrane, relying on its high elasticity, retracts synchronously with the top-pressure end face, and its surface grid-like uneven structure quickly restores its compressed and reconstructed shape, instantly restoring the adhesive force, allowing it to enter the next pick-and-release cycle. The single adhesion switching response time can be controlled within 50ms, adapting to high-speed batch transfer cycles.

[0115] (vi) Typical application scenarios

[0116] This micro-device gripping and transfer device and its matching flexible film with switchable adhesion are suitable for single or array transfer and assembly of small and fragile devices such as micro LED / mini LED chips, ultra-thin glass sheets, semiconductor silicon wafers, polymer films, and flexible electronic components. It can directly replace traditional vacuum nozzles and rigid grippers, significantly reducing the risk of defects such as edge chipping, surface scratches, and electrostatic damage. It is especially suitable for the high-precision, high-rate-of-production assembly needs of micro-devices below the hundred-micrometer level.

[0117] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A flexible membrane with switchable adhesion force based on pre-stretched femtosecond laser processing, comprising a flexible elastomer film substrate, characterized in that, At least one surface of the substrate is provided with a grid-like uneven structure formed by the intersecting arrangement of transverse and longitudinal scan lines; The grid-like concave-convex structure is formed by femtosecond laser scanning processing under a biaxial pre-tensioned state on the substrate, and completes compression reconstruction by elastic retraction as the substrate releases the pre-tension. When the flexible membrane is stretched and deformed by external force, the spacing between adjacent scanning lines of the grid-like uneven structure increases synchronously with the extension of the substrate; when the external force is removed, the spacing between adjacent scanning lines returns to its original position synchronously with the retraction of the substrate, so as to achieve reversible switching of adhesion force by changing the actual contact area with the target object.

2. The flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing according to claim 1, characterized in that, The flexible elastomer film substrate is any one of Ecoflex, PDMS, DragonSkin or SEBS-based elastomers.

3. The flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing according to claim 1, characterized in that, In the unstretched, natural state, the spacing between adjacent scan lines of the mesh-like uneven structure is 50~125μm; the thickness of the flexible elastomer film substrate is 0.5~2 mm; the surface roughness Ra of the mesh-like uneven structure increases with the number of femtosecond laser scans.

4. The flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing according to claim 1, characterized in that, The flexible membrane is configured to cause local biaxial stretching of the central contact area by back annular top pressure, thereby increasing the spacing between adjacent scan lines of the grid-like uneven structure and reducing interfacial adhesion.

5. A method for preparing a flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing, characterized in that, Includes the following steps: S1. Preparation of flexible elastomer films; S2. Fix the flexible elastomer film and apply biaxial pre-stretching to keep the film in a tensile strain state; S3. While the film is under biaxial pre-stretching tension, a femtosecond laser is used to perform transverse and longitudinal cross-scanning on the surface of the film to be processed, forming a grid-like uneven structure on the surface. S4. Release the biaxial pre-stretch, and the film elastically retracts, causing the surface grid-like uneven structure to be compressed and reconstructed, resulting in a flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing as described in any one of claims 1-4.

6. The method for preparing a switchable adhesion flexible film based on pre-stretched femtosecond laser processing according to claim 5, characterized in that, The specific content of step S1 is as follows: Mix Ecoflex A glue and B glue at a mass ratio of 1:1 and stir evenly. After vacuuming to remove air bubbles, pour into a mold and let it stand to level. Cure at 60~70℃ for 25~35 minutes. After cooling, a flexible elastomer film is obtained.

7. The method for preparing a flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing according to claim 5, characterized in that, In step S2, the displacement of biaxial pre-stretching is 10~30mm, so that the in-plane stretch ratio of the film is 1.19~1.83, and the surface of the film to be processed after pre-stretching remains flat and wrinkle-free.

8. The method for preparing a switchable adhesion flexible film based on pre-stretched femtosecond laser processing according to claim 5, characterized in that, In step S3, the processing parameters of the femtosecond laser are: repetition frequency 2~3kHz, scanning speed 50~200mm / s, and number of scans 5~20.

9. A processing system for a flexible film with switchable adhesion force based on pre-stretched femtosecond laser processing, characterized in that, The flexible membrane for manufacturing the adhesive force switchable flexible membrane based on pre-stretched femtosecond laser processing according to any one of claims 1-4, or the flexible membrane prepared by the preparation method of the adhesive force switchable flexible membrane based on pre-stretched femtosecond laser processing according to any one of claims 5-8, includes a biaxial stretching platform, a femtosecond laser processing unit, and a control unit. A biaxial stretching platform is used to hold flexible elastomer films and apply biaxial pre-stretching to the films to maintain their tensioned state. The femtosecond laser processing unit is used to output focused femtosecond laser light to the surface of the thin film to be processed and to perform scanning processing; The control unit is connected to the biaxial stretching platform and the femtosecond laser processing unit via signals, respectively. The control unit is configured to: while the film is held in a biaxial pre-stretched state, control the femtosecond laser processing unit to perform cross-scanning of the film surface in the transverse and longitudinal directions, forming a grid-like uneven structure on the film surface; and after processing, control the biaxial stretching platform to release the pre-stretch, so that the grid-like uneven structure on the film surface is compressed and reconstructed with elastic retraction.

10. A micro-device grasping and transferring device, characterized in that, Includes a transfer head body, an adhesive force switchable flexible membrane, and an annular top pressure drive assembly; The adhesive force switchable flexible film is the adhesive force switchable flexible film based on pre-stretched femtosecond laser processing as described in any one of claims 1-4, the flexible film prepared by the preparation method of the adhesive force switchable flexible film based on pre-stretched femtosecond laser processing as described in any one of claims 5-8, or the flexible film prepared by the processing system for the adhesive force switchable flexible film based on pre-stretched femtosecond laser processing as described in claim 9, which is fixed to the lower bearing end face of the transfer head body in a grid-like concave-convex structure with the surface facing outward; The annular top pressure drive assembly is located inside the transfer head body and includes an annular top pressure member that can reciprocate along the transfer head axis. The lower annular surface of the annular top pressure member faces the back center area of ​​the flexible film with switchable adhesion. When the annular top pressure component is in the retracted position, the adhesion force can be switched so that the flexible membrane remains in a natural stress-free state, exhibiting high adhesion characteristics to adsorb and pick up tiny devices. When the annular pressing member is in the extended position, it presses downward on the central area of ​​the back of the flexible membrane, causing local biaxial stretching of the corresponding area of ​​the flexible membrane. This increases the spacing between adjacent scan lines of the grid-like concave-convex structure and reduces the interfacial adhesion to release the micro-device.

Citation Information

Patent Citations

  • Conductive ink, reversible adhesion elastomer and preparation method thereof

    CN121271322A